A implementação da chamada pública de Ater agroecológica no Vale do Ribeira (PR): desafios e viabilidade - Silva, Kessy Rizental da (2017)
Rural development in Brazil has been marked by concern not only with issues related to income generation, but also with improvements in the living conditions of rural populations. Rural Extension can be configured as a tool to access public policies to promote and consolidate sustainable rural development. The present study aimed to analyze the occurrence of Ater public calls in the state of Paraná, focusing on the construction and initiation of the public call INCRA and SAF/DATER/ MDA nº 13/2013, the agroecology public call, including the perspectives of extension workers and other professionals involved in the execution of Ater activities in the region of the Vale do Ribeira. For this purpose, semi-structured interviews were applied to 17 professionals, as well as documentary and bibliographic review about the subject. Through these tools, it was possible to verify that despite significant advances in the agroecological rural extension, many bottlenecks are still present and prominent in these services. If on one hand the government presents proposals and builds with civil society structuring public policies and that leverage the life of the producer, in the other hand the state itself has stuck this development. It was also observed that in spite of the high technical and academic level presented by the extensionists in the public call for agroecological Ater, these present a high unpreparedness to deal with issues related to Agroecology, which reflects a posture still rooted in the molds of the diffusionist Ater of the 1990’s.